2011
DOI: 10.1371/annotation/138c7c99-249f-432c-a4f7-2993b7b87c0a
|View full text |Cite
|
Sign up to set email alerts
|

Correction: The Mismeasure of Science: Stephen Jay Gould versus Samuel George Morton on Skulls and Bias

Abstract: The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Yet, Gould himself was motivated to write The Mismeasure of Man by his strong political and social beliefs, which guided him to present his text describing the early intelligence scientists as blinded by their prejudices [4,7,12,50]. Given Gould’s pervasively incorrect statements in The Mismeasure of Man about the Army Beta, factor analysis [3], the place of intelligence testing in the immigration debates of the 1920s [5,9,10], the biological basis for intelligence [4,8,9], and the questions regarding Gould’s analysis of Morton’s work [11,12,13,14], we wonder whether there is any section of The Mismeasure of Man that is factually accurate.…”
Section: Overall Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, Gould himself was motivated to write The Mismeasure of Man by his strong political and social beliefs, which guided him to present his text describing the early intelligence scientists as blinded by their prejudices [4,7,12,50]. Given Gould’s pervasively incorrect statements in The Mismeasure of Man about the Army Beta, factor analysis [3], the place of intelligence testing in the immigration debates of the 1920s [5,9,10], the biological basis for intelligence [4,8,9], and the questions regarding Gould’s analysis of Morton’s work [11,12,13,14], we wonder whether there is any section of The Mismeasure of Man that is factually accurate.…”
Section: Overall Discussionmentioning
confidence: 99%
“…When Gould evaluated Samuel George Morton’s work on cranium size differences among racial groups, Gould claimed Morton selectively reported, manipulated, and distorted data in order to reach a conclusion about the supposed racial superiority of Europeans (on the basis of a larger skull capacity). Yet, Lewis et al [11] argued that Gould himself selectively reported, manipulated, and distorted data in order to bolster his argument that Morton worked to support his preconceived notions. Lewis et al’s [11] claim was contested by Weisberg [12], who argued that Lewis et al’s [11] re-analysis was flawed, and that Gould’s arguments were mostly sound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, he was famously described as 'the objectivist of his age' . 120 Gould went to great lengths to refute the science behind the Bell Curve thesis, by actively recalculating and re-analysing the statistics used by craniometrist Samuel Morton to decisively demonstrate the subjective and biased nature of Morton's calculations. He thus demonstrated that Morton's data were unreliable and distorted by his preconceived views on the intelligence of the different races.…”
Section: A Normal Historymentioning
confidence: 99%
“…Ad 9 and 10: Morton's early racial ranking of crania has a long history of recent re-examinations, including being criticized by Steven Jay Gould (1978 [36]; 1981/1996 [12,13]) and defended independently by Lewis, Degusta, Meyer, Monge, et al (2011) [17] and by Wade (2011) [37]. The latter two studies were in turn questioned in an Editorial (2011) [38], and then Weisberg (2014) [39] partially supported Gould's accusations.…”
Section: Contras To Points 7-10mentioning
confidence: 99%